Two homolog wheat Glycogen Synthase Kinase 3/SHAGGY - like kinases are involved in brassinosteroid signaling - Bittner, Thomas (BMC Plant Biol, 2015)
BACKGROUND: Glycogen Synthase Kinase 3/SHAGGY-like kinases (GSKs) are multifunctional non-receptor ser/thr kinases. Plant GSKs are involved in hormonal signaling networks and are required for growth, development, light as well as stress responses. So far, most studies have been carried out on Arabidopsis or on other eudicotyledon GSKs. Here, we evaluated the role of TaSK1 and TaSK2, two homolog wheat (Triticum aestivum) GSKs, in brassinosteroid signaling. We explored in addition the physiological effects of brassinosteroids on wheat growth and development. RESULTS: A bin2-1 like gain-of-function mutation has been inserted respectively in one of the homoeologous gene copies of TaSK1 (TaSK1-A.2-1) and in one of the homoeologous gene copies of TaSK2 (TaSK2-A.2-1). Arabidopsis plants were transformed with these mutated gene copies. Severe dwarf phenotypes were obtained closely resembling those of Arabidopsis bin2-1 lines and Arabidopsis BR-deficient or BR-signaling mutants. Expression of BR downstream genes, SAUR-AC1, CPD and BAS1 was deregulated in TaSK1.2-1 and TaSK2.2-1 transgenic lines. Severe dwarf lines were partially rescued by Bikinin beforehand shown to inhibit TaSK kinase activity. This rescue was accompanied with changes in BR downstream gene expression levels. Wheat embryos and seedlings were treated with compounds interfering with BR signaling or modifying BR levels to gain insight into the role of brassinosteroids in wheat development. Embryonic axis and scutellum differentiation were impaired, and seedling growth responses were affected when embryos were treated with Epibrassinolides, Propiconazole, and Bikinin. CONCLUSIONS: In view of our findings, TaSKs are proposed to be involved in BR signaling and to be orthologous of Arabidopsis Clade II GSK3/SHAGGY-like kinases. Observed effects of Epibrassinolide, Propiconazole and Bikinin treatments on wheat embryos and seedlings indicate a role for BR signaling in embryonic patterning and seedling growth. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-015-0617-z) contains supplementary material, which is available to authorized users.